PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MEMBENTUK SIKAP KEAGAMAAN PESERTA DIDIK DI SMA MA’ARIF BANYURESMI DAN SMK MA’ARIF GARUT - Yeni maasyrifah; Rahmat syare’i; Iis Salsabilah (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2022)
The general purpose of this study was to obtain an overview of the teacher's role in shaping the religious attitudes of students including planning, implementing, and evaluating students in the application of religion in schools. The research methodology used in this research is descriptive qualitative, to observe phenomena that appear in the field, as well as a multi-disciplinary approach, namely; pedagogical, normative theological, and sociological approaches. Data collection techniques through observation, interviews and documentation. The results of the study, that 1) the role of PAI teachers in shaping the religious attitudes of students in the two schools, instilling Islamic values ​​substantially and universally so that goals are achieved. 2) Factors that influence the formation of students' religious attitudes are: educational, social, and family factors. 3) The description of students' religious attitudes can be judged to have developed, but there is still much that needs to be addressed in fostering a comprehensive understanding of Islamic teachings, especially in the implementation of ritual worship and ethical values ​​of akhlakul karimah. (4) obstacles in shaping the religious attitudes of students, namely: a) methodological barriers covering the curriculum b) repetition of the material, c) the lack of learning media, especially teaching aids and limited time. In conclusion, that religious activities at SMA MA'arif Banyuresmi and SMK Ma'arif Garut are planned, implemented and controlled as outlined in the school work program, then religious attitudes at SMA MA'arif Banyuresmi and SMK Ma'arif Garut will increase and awareness of learning is high.